Associations of outdoor fine particulate air pollution and cardiovascular disease in 157 436 individuals from 21 high-income, middle-income, and low-income countries (PURE): a prospective cohort study. Issue 6 (June 2020) - Hystad, Perry; Larkin, Andrew; Rangarajan, Sumathy; AlHabib, Khalid F; Avezum, Álvaro; Calik, Kevser Burcu Tumerdem; Chifamba, Jephat; Dans, Antonio; Diaz, Rafael; du Plessis, Johan L; Gupta, Rajeev; Iqbal, Romaina; et al.
Summary: Background: Most studies of long-term exposure to outdoor fine particulate matter (PM2·5 ) and cardiovascular disease are from high-income countries with relatively low PM2·5 concentrations. It is unclear whether risks are similar in low-income and middle-income countries (LMICs) and how outdoor PM2·5 contributes to the global burden of cardiovascular disease. In our analysis of the Prospective Urban and Rural Epidemiology (PURE) study, we aimed to investigate the association between long-term exposure to PM2·5 concentrations and cardiovascular disease in a large cohort of adults from 21 high-income, middle-income, and low-income countries. Methods: In this multinational, prospective cohort study, we studied 157 436 adults aged 35–70 years who were enrolled in the PURE study in countries with ambient PM2·5 estimates, for whom follow-up data were available. Cox proportional hazard frailty models were used to estimate the associations between long-term mean community outdoor PM2·5 concentrations and cardiovascular disease events (fatal and non-fatal), cardiovascular disease mortality, and other non-accidental mortality. Findings: Between Jan 1, 2003, and July 14, 2018, 157 436 adults from 747 communities in 21 high-income, middle-income, and low-income countries were enrolled and followed up, of whom 140 020 participants resided in LMICs. During a median follow-up period of 9·3 years (IQR 7·8–10·8; corresponding to 1·4 million person-years), we documented 9996 non-accidental deaths, of which 3219 were attributed to cardiovascular disease. 9152 (5·8%) of 157 436 participants had cardiovascular disease events (fatal and non-fatal incident cardiovascular disease), including 4083 myocardial infarctions and 4139 strokes. Mean 3-year PM2·5 at cohort baseline was 47·5 μg/m 3 (range 6–140). In models adjusted for individual, household, and geographical factors, a 10 μg/m 3 increase in PM2·5 was associated with increased risk for cardiovascular disease events (hazard ratio 1·05 [95% CI 1·03–1·07]), myocardial infarction (1·03 [1·00–1·05]), stroke (1·07 [1·04–1·10]), and cardiovascular disease mortality (1·03 [1·00–1·05]). Results were similar for LMICs and communities with high PM2·5 concentrations (>35 μg/m 3 ). The population attributable fraction for PM2·5 in the PURE cohort was 13·9% (95% CI 8·8–18·6) for cardiovascular disease events, 8·4% (0·0–15·4) for myocardial infarction, 19·6% (13·0–25·8) for stroke, and 8·3% (0·0–15·2) for cardiovascular disease mortality. We identified no consistent associations between PM2·5 and risk for non-cardiovascular disease deaths. Interpretation: Long-term outdoor PM2·5 concentrations were associated with increased risks of cardiovascular disease in adults aged 35–70 years. Air pollution is an important global risk factor for cardiovascular disease and a need exists to reduce air pollution concentrations, especially in LMICs, where air pollution levels are highest. Funding: Full funding sources are listed at the end of the paper (see Acknowledgments).